Application-specific processor for piecewise linear functions computation - Rodríguez, Agustín Antonio (2011)
This paper presents an application specific processor architecture for the calculation of simplicial piecewise linear functions of up to six dimensions with 24-bit wide input words. The architecture, in particular registers and bus connections, is specifically designed for the task of simplicial piecewise linear computation. The parameters of the function are stored in an external 16 MB RAM memory. A proof-of-concept integrated circuit (that achieved first silicon success) was fabricated through MOSIS in a 4 mm × 4 mm 0.5 μm standard CMOS process using an automated design flow based on Synopsys and Cadence tools and the OSU standard cell library.